Моносахаридный состав полисахаридного комплекса листьев мать-и-мачехи; Бюллетень сибирской медицины; Т. 10, № 5 - Корж А. П. Анна Петровна; Гурьев А. М.; Белоусов М. В. Михаил Валерьевич; Юсубов М. С. Мехман Сулейман-оглы (Сулейманович); Белянин М. Л. Максим Львович (2011, 2011)
Заглавие с экрана